A historical analysis of critiques in the talent management debate - Paul Sparrow (BRQ Business Research Quarterly, 2019)
Current debates around talent management echo previous concern about the development of the field of IHRM. This paper uses historical analysis to examine two questions: has the field followed a logical progression and process of increasing coherence; and has its narrative been shaped in ideological ways? It identifies six concepts that guided and enabled the subsequent development of the talent management field. It shows how a selection of these ideas were re-packaged through the introduction of new notions to build two competing narratives: a star performer perspective and a human capital management perspective. It examines the progressive critiques and problems that then had to be solved to address these concerns. There is evidence of periodic ideological re-interpretations of talent management but there has nonetheless been a logical, progressive and issues-driven evolution of ideas in the field into which the current critical perspectives must now be fitted.
Keywords: 650; Human resource strategy; Talent management